2004
DOI: 10.1038/sj.onc.1207679
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 is essential for neoplastic transformation induced by both E6/E7 and E6/E7/ErbB-2 cooperation in normal cells

Abstract: More than 25% of head and neck squamous cell carcinomas (HNSCC) and 99% of cervical cancers (CxCa) are positive for high-risk human papillomaviruses (HPVs). Furthermore, the type I tyrosine kinase receptor ErbB-2 is overexpressed in at least 30% of HNSCC and CxCa. Recently, we demonstrated that E6/E7 of HPV type 16 cooperate with ErbB-2 to induce cell transformation of human normal oral epithelial (NOE) cells. This is accompanied by overexpression of cyclin D1 in NOE cells. To determine the role of cyclin D1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 25 publications
(37 reference statements)
3
33
0
Order By: Relevance
“…To study the role of specific BRCA1 gene mutations in human breast carcinogenesis, primary human normal and BRCA1-mutated (3450delCAAG) mammary epithelial cell lines, HNME and BB2, were established in our laboratory; these cell lines were immortalized using E6/E7 of HPV type 16 retro-vectors as described by Al Moustafa et al 10 Moreover, we transfected these cell lines with the full length BRCA1 gene. We confirmed that these cells overexpress/express BRCA1 and E6/E7 by western blot and RT-PCR (data not shown).…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…To study the role of specific BRCA1 gene mutations in human breast carcinogenesis, primary human normal and BRCA1-mutated (3450delCAAG) mammary epithelial cell lines, HNME and BB2, were established in our laboratory; these cell lines were immortalized using E6/E7 of HPV type 16 retro-vectors as described by Al Moustafa et al 10 Moreover, we transfected these cell lines with the full length BRCA1 gene. We confirmed that these cells overexpress/express BRCA1 and E6/E7 by western blot and RT-PCR (data not shown).…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…In this model, we established that E6/E7 oncoproteins of high-risk type 16 cooperate with the ErbB-2 receptor to induce cellular transformation of HNE cells; this was accompanied by a delocalization of β-catenin from the undercoat membrane to the nucleus in HNE cells. Furthermore, we reported that cyclin D1 is the target of E6/E7/ErbB-2 cooperation via the conversion of β-catenin's role from a cell-cell adhesion molecule to a transcriptional regulator [96]. In parallel, we revealed that D-type cyclins (D1, D2, and D3) are essential for cell transformation induced by E6/E7/ ErbB-2 cooperation in human HNE and mouse normal embryonic fibroblast (NEF) cells [96,97].…”
Section: High-risk Hpvs In Colorectal Cancersmentioning
confidence: 67%
“…Furthermore, we reported that cyclin D1 is the target of E6/E7/ErbB-2 cooperation via the conversion of β-catenin's role from a cell-cell adhesion molecule to a transcriptional regulator [96]. In parallel, we revealed that D-type cyclins (D1, D2, and D3) are essential for cell transformation induced by E6/E7/ ErbB-2 cooperation in human HNE and mouse normal embryonic fibroblast (NEF) cells [96,97]. Finally, we were able to show that the cooperation effect of E6/E7 with ErbB-2, in human normal epithelial and cancer cells, occurs via β-catenin tyrosine phosphorylation through pp60 (c-Src) kinase activation [98,99].…”
Section: High-risk Hpvs In Colorectal Cancersmentioning
confidence: 99%
“…Their inhibition allows cells harboring genomic damage to survive and to evolve into cancer cells, instead of a fate of elimination and eradication [23,24]. Recent studies indicate that the cancer process is enhanced by estrogen (see Discussion below).…”
Section: Discussionmentioning
confidence: 99%